Legal Metaphors in the Epistles - Lyall, Francis (1981)
The technicalities of Roman law have much to offer in considering some of the language of the epistles.
Keywords: romans; 1 corinthians; roman law; legal metaphors; Metaphor; Epistles; New Testament